PERANCANGAN SISTEM INFORMASI PENJUALAN GADGET DI PT. KAFILAH TEKNOLOGI INDONESIA - Naufaludin Akbar; Dendy Kurniawan (Jurnal Riset Teknik Komputer, 2024)
The research objective is to produce a gadget sales information system that can simplify the process of recording sales data to sales reports. According to observations and interviews that the author did at PT Kafilah Teknologi Indonesia in processing gadget sales data, all of which still use the manual method, namely recording in the books so that errors often occur. in calculating reporting and which often vary, this can hamper the process of financial reporting performance. The research method used in the Design of Gadget Sales Information Systems at PT. This Indonesian Technology Caravan is grounded research, which is a research method based on facts and using comparative analysis which aims to generalize epirisses, establish concepts, prove theories, and develop theories where data collection and data analysis run at the same time. In addition, the authors also conducted research with data collection methods by means of Observation, Interview and Documentation. After the author designed the Gadget Sales Information System, the author can help build a prototype so that the results are useful for the company so that it is expected to be more effective and accurate.